Nanoparticulate Systems for Bioactive Agent Delivery: What Is the Missing Link in Research for Real Applications?. Issue 5 (22nd February 2021) - Lai, Wing-Fu; Wong, Wing-Tak
Abstract : Diverse nanoparticulate systems, ranging from polymeric nanoparticles to liposomes, have been exploited as carriers of bioactive agents in recent years; however, the use of these systems has been confined largely to the laboratory context till now. Systems that can successfully be adopted for bioactive agent delivery in practice are few. Herein, such low efficiency in clinical translation is partly due to the lack of awareness of the similar nature between a carrier and a real drug. To rectify this situation, it is important to treat a carrier as an ordinary drug despite its absence of therapeutic effects. The current situation in prevalent bioactive agent delivery research, as well as those routine research practices that should be changed to enhance clinical translation, will be discussed here. Abstract : Diverse nanoparticulate systems have been exploited as carriers of bioactive agents over the years; however, systems that can finally get to real applications are few. Such low efficiency in clinical translation is partly due to the lack of awareness of the similar nature between a carrier and a real drug.